Evaluation and optimization of textile ultrasonic welds for textile temperature control elements using transient thermal numerical analysis - Alexander Reich; Yordan Kyosev; Hassan Saeed (Communications in Development and Assembling of Textile Products)
Ultrasonic welding is an efficient method of joining thermoplastic fabrics or other textile semi-finished products in a watertight manner. It is applied in the making of functional clothing, such as chemical protective clothing, sportswear or smart clothing, or other technical products. Another special field of application developed at the Chair of Development and Assembly of Textile Products is the use of coated textiles as temperature control elements. For this type of product, it is necessary to design the ultrasonic welds in such a way that the media-tight coating is not damaged and the joint is continuous. This paper presents the option of evaluating and optimizing the ultrasonic welding process for the production of the textile tempering systems using transient thermal analysis in order to improve the overall quality of the seam and ensure media tightness along the seam.